2018
DOI: 10.1101/254359
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Antagonism between the dynein and Ndc80 complexes at kinetochores controls the stability of kinetochore-microtubule attachments during mitosis

Abstract: Chromosome alignment and segregation during mitosis depends critically on kinetochoremicrotubule (kMT) attachments that are mediated by the function of the molecular motor cytoplasmic dynein, and the kinetochore microtubule (MT) binding complex, Ndc80. The RZZ (Rod-ZW10-Zwilch) complex is central to this coordination as it has an important role in dynein recruitment and has recently been reported to have a key function in the regulation of stable kMT attachment formation in C. elegans. However, the mechanism b… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…We first confirmed the localization to these proteins to prometaphase kinetochores during early mitosis (Fig S2A). Next, we disrupted their function by treating with specific siRNAs and employing published protocols (Amin et al, 2015; Amin et al, 2018; Kiyomitsu et al, 2007). We confirmed the efficiency of depletion of the target proteins by immunoblotting (Fig S2B).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We first confirmed the localization to these proteins to prometaphase kinetochores during early mitosis (Fig S2A). Next, we disrupted their function by treating with specific siRNAs and employing published protocols (Amin et al, 2015; Amin et al, 2018; Kiyomitsu et al, 2007). We confirmed the efficiency of depletion of the target proteins by immunoblotting (Fig S2B).…”
Section: Resultsmentioning
confidence: 99%
“…It has been previously shown that chromosomes captured by spindle microtubules move poleward rapidly, via lateral kMT attachments and motility mediated by dynein (Rieder and Alexander, 1990; Vorozhko et al, 2008; Yang et al, 2007). In vitro analysis showed that microtubule-binding to kinetochores is reduced by dynein/dynactin inhibition (Vorozhko et al, 2008), and that kinetochore dynein prevents premature stabilization of load-bearling, end-on kMT attachments (Amin et al, 2018; Barisic and Maiato, 2015; Cheerambathur et al, 2013; Gassmann et al, 2008). Our data suggest that dynein, however, is not required for a large fraction of initial kMT attachments that are formed during early mitosis in Human cells (Fig S2C, D).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations